Perumusan Strategi Dalam Menentukan Arah Pengembangan Bisnis Pada PT.Cepa - Adrianus Aprilius (Musamus Journal of Business & Management, 2019)
This research aims to formulate a strategy that will be used by PT. Cepa in developing its business in the Operation & Maintainance Power Plant and Mini LNG Plant service industries. This study uses a corporate strategy formulation to be able to develop and be sustainable by formulating its business strategy. In the input stage using the IFE and EFE Matrix method and continued with the analysis phase using the SWOT Matrix and IE to generate alternative strategies. Then the results are processed using the QSPM matrix, so an alternative strategy is right for the company. The results of the total attractive score (TAS) research based on the QSPM method show that alternative strategies in accordance with the current condition of the company are the development of O&M products / services with the highest score of 5.552 higher than the O&M market development with a score of 5.280 and backward integration is carried out by making special contracts to the OEM supplier (original equipment manufacture) with a score of 5.202. Keywords: Strategy Formulation, SWOT, QSPM